Levels and Significance of Tumor Markers and Cytokines in Serum and Peritoneal Lavage Fluid of Patients with Peritoneal Metastasis of Gastric Cancer. (2nd June 2022) - Yang, Jianqi; Cao, Wenmiao; Xing, Enming
Abstract : The paper is written to investigate the levels and significance of tumor markers [carcinoembryonic antigen (CEA), carbohydrate antigen 125 (CA125), and carbohydrate antigen 19-9 (CA19-9)] and cytokines [interleukin-6 (IL-6), IL-4, and IL-2] in serum and peritoneal lavage fluid of patients with peritoneal metastasis of gastric cancer. For this research, 145 patients with gastric cancer treated in our hospital were divided into peritoneal metastasis group (n = 25 ), other metastasis group (n = 32 ), and nonmetastasis group (n = 88 ) according to the occurrence of metastasis. At the same time, the levels of serum tumor markers and cytokines and tumor markers and cytokines in intraoperative peritoneal lavage fluid were compared among the three groups. The results showed that the proportion of TNM stage III in peritoneal metastasis group and other metastasis group was 68.00% and 62.50%, respectively, and the proportion of tumor >5 cm was 64.00% and 59.38%, respectively, which was significantly higher than that in the control group. The 1-year survival rate of peritoneal metastasis group and other metastasis group was 44.00% and 40.63%, respectively, which was significantly lower than that of nonmetastasis group (P < 0.05 ).The serum levels of CEA, CA125, CA19-9, IL-6, IL-4, and IL-2 in peritoneal metastasis group and other metastasis group were higher than those in nonmetastasis group. The intraoperative peritoneal lavage fluid CEA, CA125, and IL-6 were 13.41 ± 3.72  ng/ml, 8.97 ± 1.33  U/ml, and 1.85 ± 0.44  pg/ml, respectively, which were higher than those in other metastasis groups and nonmetastasis groups (P < 0.05 ). There was no significant difference in the levels of CA19-9, IL-4, and IL-2 in peritoneal lavage fluid among peritoneal metastasis group, other metastasis groups, and nonmetastasis groups (P > 0.05 ); the areas under the ROC curve of intraoperative peritoneal lavage fluid CEA, CA125, and IL-6 in predicting peritoneal metastasis were 0.850, 0.902, and 0.806, respectively, P < 0.05 . Thus, the conclusion is that peritoneal lavage fluid CEA, CA125, and IL-6 have certain application value in predicting and diagnosing peritoneal metastasis of gastric cancer, while the other indexes have no application value.